Acral necrosis by Stenotrophomonas maltophilia - PEREIRA, O. (2010)
Keywords:necrosis;skin and soft tissue infection;Stenotrophomonas maltophilia Abstract Background Stenotrophomonas maltophilia (SM) has been considered a nosocomial pathogen. Nevertheless, community acquired infection may occur more frequently than usually recognized. Case We describe distal necrosis of the fingers by SM in a farmer, contracted in the community and successfully treated with a combination of cotrimoxazole and ciprofloxacin. The patient was diagnosed with chronic lymphocytic leukaemia 6 months later. Conclusions This unusual presentation shows that infection with SM should be included in the differential diagnosis of the skin and soft tissue infection, even in apparently healthy patients.